SOCIAL RESPONSIBILITY IN THE SYSTEM OF "MAN-NATURE" AS A SOCIAL VALUE IN THE EDUCATION OF YOUTH - Ashytok, Nadiia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The solution to the global environmental problems of humanity should be dictated by practical production, scientific and technical inventions, and, moreover, the changes in the spiritual sphere. In this regard, the issues of education, change of values, and the formation of a responsible attitude to the world are of paramount importance. The aim of the article is to study the phenomenon of social responsibility in the system of "man-nature", and its task correspondently is to consider the features of the formation of social responsibility as a social value in the context of environmental education. Research methods. General scientific and special research methods were used in the study. The system method was used as the leading one to study the object under research within a holistic set of its elements and their relations. In addition, the methods of induction, deduction, analysis, synthesis, generalization, and others were used in the study. Research results. Environmental education is closely related to moral education because the formation of a new attitude of man to nature is not so much a socio-economic but a moral task. The final aim of environmental education is the formation of a responsible attitude to nature, which involves compliance with moral and legal principles in activities aimed at studying nature, and its protection. In the article, the formation of this value is studied in the environmental, moral, and regulatory aspects. Discussion. E. Giddens believes that modernity, which constantly involves an individual in a state of value choice, changes the content of interpersonal relations. As a result, there is a disorientation of people, the source of which is the rupture of the continuity of social and cultural traditions. In the opinion of the author, social and cultural traditions do not lose the status of external pillars, despite the fact that social responsibility is of particular importance. Conclusion. Modern civilization is characterized to be contradictory, its development is associated with the progressive movement but also with the growing environmental crisis, which can be overcome due to value changes in human consciousness, and awareness of social responsibility for the future of mankind.